1992
DOI: 10.1007/bf00570888
|View full text |Cite
|
Sign up to set email alerts
|

A free-radical hypothesis for the instability and evolution of genotype and phenotypein vitro

Abstract: It has been known for several decades that cultured murine cells undergo a defined series of changes, i.e., an in vitro evolution, which includes crisis, spontaneous transformation ('immortalization'), aneuploidy, and spontaneous neoplastic transformation. These changes have been shown to be caused by the in vitro environment rather than an inherent instability of the murine phenotype or genotype. Serum amine oxidases were recently identified as a predominant cause of crisis. These enzymes generate hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 212 publications
0
5
0
Order By: Relevance
“…Most anchorage-dependent cell lines had generation times of ≈12 h in the exponential growth phase. This is the optimum for rodent cells in vitro (Parchment and Natarajan, 1992). For other serum-free media generation times of ≈24 h were reported (Gasser et al, 1985;Lee et al, 1996;Renner et al, 1995;Sharif and Stevenson, 1993;Sinacore et al, 1996).…”
Section: Growth Characteristics In Serum-free Medium Cho-t1-sfmentioning
confidence: 80%
“…Most anchorage-dependent cell lines had generation times of ≈12 h in the exponential growth phase. This is the optimum for rodent cells in vitro (Parchment and Natarajan, 1992). For other serum-free media generation times of ≈24 h were reported (Gasser et al, 1985;Lee et al, 1996;Renner et al, 1995;Sharif and Stevenson, 1993;Sinacore et al, 1996).…”
Section: Growth Characteristics In Serum-free Medium Cho-t1-sfmentioning
confidence: 80%
“…Although they have high self-renewal capacity, dental stem cells such as SHED will ultimately enter an irreversible proliferation-arrested state referred to as replicative senescence after long term in vitro culture under culture stresses, such as hyperoxia and elevated temperature [ 6 ]. Several strategies have been explored to overcome this replicative senescence, such as treatment of SHED with benzopyrene (BaP), radiation, or ectopic expression of viral oncogenes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several groups have recently provided indirect evidence that amine oxidases may be involved in tumorigenesis via production of reactive aldehydes and hydrogen peroxide [16,17]. Moreover, in earlier studies it has been demonstrated that hydrogen peroxide produced by amine oxidases may cause spontaneous neoplastic transformation of cultivated murine cells in vitro [3]. Notably, it seems that the specific activities of aldehyde dehydrogenases are reduced in benign prostate hyperplasia, as well as in prostate tumours [18].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of these substrates yields formaldehyde and methylglyoxal respectively. In contrast with a protective role of SSAOs, it has been proposed by several investigators that reactive aldehydes and hydrogen peroxide produced by endogenous amine oxidases could be of importance with regard to carcinogenesis [3,4].…”
Section: Introductionmentioning
confidence: 97%